Investigation on the pore structure and multifractal characteristics of tight oil reservoirs using NMR measurements: Permian Lucaogou Formation in Jimusaer Sag, Junggar Basin - Zhao, Peiqiang; Wang, Zhenlin; Sun, Zhongchun; Cai, Jianchao; Wang, Liang (Marine and petroleum geology, 2017)
Pore structure is a critical parameter to estimate the reservoir quality and evaluate the resource potential. However, the pore structure and heterogeneity of the unconventional tight oil reservoirs of Permian Lucaogou Formation of Jimusaer Sag, Junggar Basin are not studied well. In this paper, the multifractal analysis based on the NMR T2 distributions was applied to investigate the pore structure and heterogeneity. The reservoir quality index (RQI) and flow zone indicator (FZI) were calculated using porosity and permeability. Two parameters T35 and T50 were newly defined as relaxation times corresponding to the 35% and 50% saturation on the T2 reverse accumulative curve, respectively. The results showed that the RQI, and FZI values were extremely low, and that the NMR T2 distributions of water saturated samples had much short relaxation components with no or little long relaxation components, indicating a complex and poor microscopic pore structure of tight oil rocks. The typical multifractal characteristics, such as the large values of singularity strength range (Δα), revealed that the pore structures of samples were strongly heterogeneous. It was also found that the clay contents have an obvious influence on the multifractal parameters, and the FZI and new defined T35 are two good indicators for heterogeneity of pore structure. In addition, the feasibility and applicability of calculating the multifractal parameters from NMR and other well logs were discussed. •The pore structure of Lucaogou tight oil formation was studied by NMR measurements.•The heterogeneity of pore structure was investigated by multifractal analysis.•Two new parameters (T35and T50) were defined to characterize the rock property.•The FZI and T35 are good indicators for heterogeneity of pore structure.